Pengaruh Pengaruh Pendampingan Suami Terhadap Tingkat Kecemasan Ibu Bersalin Di UPT RSUD Kabupaten Kepulauan Meranti - Maula, Syahroza; Susanti, Komaria; Oktora, Ary; Aifa, Wira Ekdeni (Jurnal Kesehatan Abdurrahman, 2026)
Childbirth is a physiological process that is often accompanied by psychological changes, one of which is anxiety experienced by laboring mothers. High levels of anxiety may negatively affect the progress of labor as well as maternal and neonatal outcomes. Husband support is considered an important factor in reducing maternal anxiety during childbirth. This study aimed to determine the effect of husband support on the anxiety level of laboring mothers at UPT RSUD Kabupaten Kepulauan Meranti in 2025. This research employed an analytic correlational design with a cross-sectional approach. The study population consisted of all laboring mothers at UPT RSUD Kabupaten Kepulauan Meranti in June 2025, totaling 28 respondents, using a total sampling technique. Data were collected using a respondent characteristic questionnaire and the Hamilton Anxiety Rating Scale (HARS). Data analysis was conducted through univariate and bivariate analyses using the Chi-Square test and Linear-by-Linear Association. The results showed that 67.9% of respondents did not receive husband support during childbirth, while 32.1% received husband support. Most respondents experienced mild anxiety (53.6%), followed by no anxiety (39.3%) and moderate anxiety (7.1%). The Chi-Square test yielded a p-value of 0.106, while the Linear-by-Linear Association test showed a p-value of 0.040, indicating a tendency toward decreased anxiety levels with increased husband support. In conclusion, husband support tends to reduce anxiety levels among laboring mothers. Therefore, healthcare providers are encouraged to promote husband involvement during childbirth to improve maternal psychological well-being and the quality of midwifery care.